2011
DOI: 10.1080/02603594.2011.608443
|View full text |Cite
|
Sign up to set email alerts
|

“SOFT OXOMETALATES” (SOMs): A VERY SHORT INTRODUCTION

Abstract: Abstract.The field of polyoxometalates (POMs) [1] , in recent times, has entered a new arena of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…Research has been focused on the development of novel materials which synergistically combine "hard" POMs with a range of "soft", mostly organic materials to form novel compounds. [45][46][47] Their usage as catalysts, sensors and electrochemically active materials is shortly discussed in this chapter, with three literature examples to give insight into the current frontiers of POM-IL research.…”
Section: The Merits Of Pom-ils Exemplified By State-of-the-art Researchmentioning
confidence: 99%
“…Research has been focused on the development of novel materials which synergistically combine "hard" POMs with a range of "soft", mostly organic materials to form novel compounds. [45][46][47] Their usage as catalysts, sensors and electrochemically active materials is shortly discussed in this chapter, with three literature examples to give insight into the current frontiers of POM-IL research.…”
Section: The Merits Of Pom-ils Exemplified By State-of-the-art Researchmentioning
confidence: 99%
“…4b; 15 Until recently, POMs have hardly been connected to the¯eld of soft materials; pioneering work on soft oxometalate S. Herrmann, A. Seliverstov & C. Streb materials (SOMs) started at the end of the 20th century and has quickly developed into a thrivinḡ eld. 5 Research has been focused on the development of novel materials which synergistically combine \hard" POMs with a range of \soft", mostly organic materials to form novel compounds with soft matter properties. 5,16 In a way, liquids could be described as the ultimate soft material, and the development of the promising, yet young class of polyoxometalate-ionic liquids will be described here.…”
Section: Polyoxometalate Ionic Liquids (Pom-ils)mentioning
confidence: 99%
“…5 Research has been focused on the development of novel materials which synergistically combine \hard" POMs with a range of \soft", mostly organic materials to form novel compounds with soft matter properties. 5,16 In a way, liquids could be described as the ultimate soft material, and the development of the promising, yet young class of polyoxometalate-ionic liquids will be described here. POM-ILs 17 are obtained when anionic POM clusters are combined with a range of organic bulky cations to give versatile materials which are liquid at or around room temperature.…”
Section: Polyoxometalate Ionic Liquids (Pom-ils)mentioning
confidence: 99%
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 98%